Measuring empathy in medical students: A cross-sectional study - Iqbal, Muhammad Zafar; Riyadh AlBuraikan, Areej; Abdullah AlQarni, Afnan; Abdulaziz AlQahtani, Hanan; Mohammad AlOhali, Alyaa; Mohammed AlMusaileem , Malak (Journal of the Pakistan Medical Association, 2022)
Objective: To measure the empathy levels of undergraduate medical students, and to explore whether the empathy level has any significant association with gender, academic year and academic achievement. Methods: The cross-sectional study was conducted at the College of Medicine, Imam Abdulrahman Bin Faisal University, Dammam, Saudi Arabia, from January to March 2020, and comprised medical students. Data was collected using the pre-validated student version of the Jefferson Scale of Empathy. Data was analysed using SPSS 23. Results: Of the 391 students, 251(64.19%) were females, and 140(35.8%) were males. The overall mean empathy score was 105.18+/-12.51. Second year medical students showed the highest empathy score 108.59+/-13.33. There was minor but significant decline in empathy as the students progressed through their academic studies (p<0.05). Empathy scores were significantly higher in female students (p<0.05), and students with higher grade point average scores (p<0.05). Conclusion: The gradual reduction in empathy is alarming and demands due attention.